The effects of potential land development on agricultural land prices - Andrei J. Plantinga; Ruben N. Lubowski; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2002)
We conduct a national-scale study of the determinants of agricultural land values to better understand how current farmland prices are influenced by the potential for future land development. The theoretical basis for the empirical analysis is a spatial city model with stochastic returns to future land development. From the theoretical model, we derive an expression for the current price of agricultural land in terms of annual returns to agricultural production, the price of recently developed land parcels, and expressions involving model parameters that are represented in the empirical model by nonlinear functions of observed variables and parameters to be estimated. We estimate the model of agricultural land values with a cross-section on approximately three thousand counties in the contiguous U.S. The results provide strong support for the model, and provide the first evidence that option values associated with irreversible and uncertain land development are capitalized into current farmland values. The empirical model is specified in a way that allows us to identify the contributions to land values of rents from near-term agricultural use and rents from potential development in the future. For each county in the contiguous U.S., we estimate the share of the current land value attributable to future development rents. These results give a clearer indication of the magnitude of land development pressures and yield insights into policies to preserve farmland and associated environmental benefits.
Keywords: 330; land use; option value; Landwirtschaftliche Immobilien; Grundstückserschließung; Bodenpreis; Stadtökonomik; Theorie; USA